Assessment of the Microbial Quality of Sachet Water Sold in New Nyanya, Nasarawa State, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
Sachet water is a widely consumed source of drinking water in Nigeria due to its affordability and accessibility, particularly in urban and semi-urban areas. However, concerns about its microbial safety persist. This study assessed the microbial quality of sachet water sold in New Nyanya area of Karu Local Government, Nasarawa State. 20 sachet water samples were randomly collected from different vendors and analysed for microbial contamination using the Most Probable Number (MPN) method. The pH values of all samples ranged between 7.4 and 8.1, which falls within the World Health Organization's recommended limits for drinking water (6.5 – 8.5). However, microbial analysis revealed coliform contamination in two brands (F and I), with Brand I showing a significantly high coliform count of 43 MPN/100ml – far exceeding the permissible limit of 0 MPN/100ml. Biochemical identification of the isolates confirmed the presence of potentially pathogenic organisms such as Shigella spp., Klebsiella pneumoniae, Salmonella spp., and Pseudomonas aeruginosa. These findings highlight the potential public health risks associated with the consumption of contaminated sachet water and underscore the need for stricter regulatory oversight, improved quality control during production, and increased public awareness regarding water safety.